Effect of Partial Organic Fertilizer Substitution on Heavy Metal Accumulation in Wheat Grains and Associated Health Risks - Liu, Yumin; Ma, Ronghui; Yang, Yan; Wang, Jiangnan; Guan, Xilin; Wang, Mei; Li, Ni; Xu, Yu; Jiang, Lihua (Agronomy (Basel), 2023)
The partial substitution of chemical fertilizers with organic manure is an important strategy for improving agricultural sustainability. However, its effect on heavy metal (HM) pollution and its potential risk to human health remain unclear. Therefore, a field study was conducted to evaluate the effects of partial organic fertilizer substitution (0, 10%, 20%, 30%, and 40%) on health risks posed by HMs, including Zn, Cu, Ni, Cd, Pb, As, and Cr. The results showed that organic fertilizer substitution significantly increased Cu, Cd, Pb, and As accumulations in the soil. The Zn, Cu, Pb, and As contents were significantly higher in grains grown under organic fertilizer substitution (40%) conditions. The HM contents in the soil and grains were below the safety threshold limits in all treatments. Furthermore, the health risk caused by the exposure to As, Cu, and Zn accounted for 86% of the hazard index (HI) value. The HI value was significantly greater at a substitution ratio of 40% than in the no-nitrogen fertilizer treatment. Ingestion of the wheat grains grown at substitution ratios ≥ 30%) increased the carcinogenic risk of As and the total carcinogenic risk. In conclusion, organic fertilizer substitution at high ratios significantly increased the non-carcinogenic and carcinogenic risks associated with ingesting wheat grain. The optimal organic fertilizer substitution ratio (20%) maintained crop yields and improved soil fertility without increasing the non-carcinogenic or carcinogenic risks to human health. These findings highlight the importance of understanding the impacts of optimal organic fertilizer management in wheat growing systems.